Acquired and Innate Immunity Impairment and Severe Disseminated Mycobacterium genavense Infection in a Patient With a NF-κB1 Deficiency - Gonzalez-Granado, Luis Ignacio; Ruiz-García, Raquel; Blas-Espada, Javier; Moreno-Villares, José Manuel; Germán-Diaz, Marta; López-Nevado, Marta; Paz-Artal, Estela; Toldos, Oscar; Rodriguez-Gil, Yolanda; de Inocencio, Jaime; Domínguez-Pinilla, Nerea; Allende, Luis M. (Frontiers in Immunology, 2019)
Background: NF-kB1 is a master regulator of both acquired and innate responses. NFKB1 loss-of-function mutations elicit a wide clinical phenotype with asymptomatic individuals at one end of the spectrum and patients with common variable immunodeficiency, combined immunodeficiency or autoinflammation at the other. Impairment of acquired and innate immunity and disseminated Mycobacterium genavense infection expands the clinical and immunological phenotype of NF-κB1 deficiency. Objective: Functional and molecular characterization of a patient with a novel phenotype of NF-kB1 deficiency. Methods: Circulating T, B, dendritic cell subsets and innate or unconventional T-cells were quantified. The cytokine production in stimulated whole blood samples was assessed and molecular characterization by next generation sequencing and gene expression assays were also performed. Results: We report a patient presenting with features of combined immunodeficiency (CID) and disseminated Mycobacterium genavense infection. Sequencing of genomic DNA identified a novel synonymous mutation (c.705G>A) in NFKB1 gene which resulted in exon 8 skipping and haploinsufficiency of the NF-kB1 subunit p50. The susceptibility to atypical mycobacterial infection has not been previously reported and may be the result of a dendritic cell deficiency. A selective deficiency of circulating follicular helper T (cTFH) cells responsible for mediating the differentiation of naive B cells into memory and plasma cells was also present in the patient. It could affect the maturation of innate or unconventional T cells where NF-kB1 could also be involved. Conclusion: These findings showed that the role of NF-κB1 in humans could be critical for the development of acquired and innate immunity and further highlights the role of human T cells in anti-mycobacterial immunity.